Metabolický syndrom a skrytá deprese v populacním vzorku - Hess, Z; Rosolová, H; Podlipný, J; Holubec, L; Topolcan, O; Petrlová, B (Casopis lekaru ceskych, 2004)
BACKGROUND: The aim of study was to reveal the relationship between metabolic syndrome and depression in a population sample, based on clinical and metabolic parameters. METHODS AND RESULTS: We tried to estimate depression (or other psychopathologies) prevalence in a randomly chosen population sample of the Pilsen city, using special questionnaires. Further, we estimated metabolic syndrome of insulin resistance risk factors and we looked for the relationship between these two disorders. Mental state of object was classified according to the questionnaires results, currently evaluated by the psychiatrist. Metabolic syndrome of insulin resistance was diagnosed as a presence of 3 of the 5 following factors: Triglycerides > or = 1.7 mmol/l, HDL cholesterol < 1.0 mmol/l in males or < 1.3 mmol/l in females, blood pressure > or = 130/85 mmHg (and/or antihypertensive medication), fasting plasma glucose > or = 6.1 mmol/l, waist circumference >102 cm in males or > 88 cm in females. Depressive syndrome diagnosed by Zungs scale is present in 31% of the Pilsen population, in 38% females and 31% males (n = 340). In the group of depressive objects, characteristics of metabolic syndrome of insulin resistance were two times higher than in the control group. Differences in resting heart rate, triglycerides level and fasting C-peptid were significantly higher in the depressive subjects. After the corrections considering age, sex and treatment adjustment, the waist to hip ratio was in the depressive subjects statistically higher as well as the 24 hour excretion of urine cortisone. In persons with metabolic syndrome of insulin resistance the prevalence of depression and anxiety was significantly higher. CONCLUSIONS: Our results show a possible relationship between depressive disorder and risk factors of the syndrome of insulin resistance. The question remains if the depression treatment can correct some of the metabolic syndrome risk factors.
Keywords: metabolický syndrom; Female; rizikové faktory; Depression; Humans; ženské pohlaví; mužské pohlaví; Male; lidé; deprese; lidé středního věku; Middle Aged; Metabolic Syndrome; Risk Factors